2017
DOI: 10.1001/jamaneurol.2017.1310
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pregnancy and Perinatal Outcomes Among Women With Epilepsy

Abstract: IMPORTANCE To date, few attempts have been made to examine associations between exposure to maternal epilepsy with or without antiepileptic drug (AED) therapy and pregnancy and perinatal outcomes.OBJECTIVES To investigate associations between epilepsy in pregnancy and risks of pregnancy and perinatal outcomes as well as whether use of AEDs influenced risks. DESIGN, SETTING, AND PARTICIPANTSA population-based cohort study was conducted on all singleton births at 22 or more completed gestational weeks in Sweden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 36 publications
(78 reference statements)
4
90
2
4
Order By: Relevance
“…Women on antiepileptic drugs during pregnancy are able to have a normal and favourable outcome 3. Some studies suggest increased risks of both congenital malformations and impaired neurodevelopment across cognitive, motor and behavioural domains among offspring exposed to antiepileptic drugs in utero 4–8.…”
Section: Introductionmentioning
confidence: 99%
“…Women on antiepileptic drugs during pregnancy are able to have a normal and favourable outcome 3. Some studies suggest increased risks of both congenital malformations and impaired neurodevelopment across cognitive, motor and behavioural domains among offspring exposed to antiepileptic drugs in utero 4–8.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Razaz et al demonstrate through linked data analysis that AEDs did not increase the risk of complications in live births >22 weeks gestation, including congenital malformations 3. Artama et al used data from the Finnish National Health Register (1996–2008) to examine the outcomes of 4867 live and still births of women with epilepsy and exposed to AEDs (3067, 63%) and found that AED treatment (n=1800) only slightly increased the risk of admission into a neonatal care unit 4.…”
Section: Commentarymentioning
confidence: 65%
“…Razaz et al 3 used linked administrative data to determine perinatal outcomes for women diagnosed with epilepsy from hospital inpatient and outpatient records in Sweden between 1997 and 2011. A subset of women who were treated with AEDs 30 days before the estimated date of conception to birth between 2005 and 2011 were also identified from the Prescribed Drug Registry and their outcomes were assessed with propensity scoring to optimise adjustment for covariates such as maternal habitus and physical and psychiatric comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of preterm delivery has been reported to be almost increased 2‐fold in WWE, but this was not reported in all studies . Prematurity is obviously increased in AED‐exposed infants, especially in those with polytherapy treatment …”
Section: Ethnicity In the Current Pregnancy Research Initiatives Of Wwementioning
confidence: 92%